Competition between Multiproduct Firms with Heterogeneous - Roson, Roberto (Advances in Social Sciences Research Journal, 2015)
This paper draws upon Feenstra and Ma (2007, 2008), to develop a model of asymmetric competition between multiproduct firms. The model is used to analyze how cost asymmetry affects the equilibrium, with determination of quantity/price as well as product scope per firm. By treating the number of firms as a continuous variable, the model is extended to account for the endogenous determination of the number of firms in a long-run, monopolistically competitive equilibrium, with free entry by heterogeneous firms.